Strengthening Community Services Based On Sustainable Ecotourism With A Business Acumen Focus In The Nipah Beach Conservation Area: A Collaborative Initiative Between University of Mataram and Universiti Utara Malaysia - Eni Indriania; Nurabiah Nurabiah; Lukman Effendy; Azril Osa Afgani; Lalu Muhammad Alwi; Sahrul Irsan (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2024)
This international community engagement activity, a collaborative endeavor between the Faculty of Economics and Business (FEB) University of Mataram (Unram), Indonesia, and Universiti Utara Malaysia (UUM), Malaysia, strategically focused on bolstering community services through sustainable ecotourism in the Nipah Beach conservation area, North Lombok Regency, Indonesia. A core objective was to integrate business acumen and financial literacy into conservation efforts, empowering local communities to develop viable, environmentally responsible enterprises. Held on November 10, 2024, the initiative brought together lecturers and students from the Diploma III Accounting program at FEB Unram and their counterparts from UUM. Key activities included an in-depth session on sea turtle conservation, a comprehensive discussion on business opportunities within sustainable ecotourism, an introductory workshop on financial literacy for small-scale ventures, and the symbolic release of juvenile turtles. This article meticulously details the project's conceptualization, planning, implementation, and potential long-term impacts, emphasizing its novel contribution to environmental preservation, local economic empowerment, and the cultivation of international academic and entrepreneurial collaboration.